Erosion of bowel by catheter of peritoneal access device during intraperitoneal chemotherapy: A case report and PRISMA-driven systematic review. Issue 2 (2016) - Lin, Hung-Hsin; Cheng, Hou-Hsuan; Chang, Yi; Chang, Yen-Hou; Chuang, Chi-Mu
No abstract available